Poverty and Gender Inequality on GRDP per Capita in Indonesia: A Path Analysis - Berliyani, Diana; Marselina, Marselina; Taher, Arivina Ratih Yulihar (Revenue Journal: Management and Entrepreneurship, 2025)
This study investigates the impact of poverty and the Gender Inequality Index (GII) on Indonesia’s Gross Regional Domestic Product (GRDP) per capita across 34 provinces using secondary data from the Central Bureau of Statistics (BPS) for the years 2021–2023. Employing path analysis, the study examines both the direct and indirect effects of poverty and gender inequality on regional economic performance. The findings reveal that the poverty rate significantly negatively affects GRDP per capita, with a path coefficient of -0.305, indicating that higher poverty levels are associated with lower economic output per person. Furthermore, the GII significantly affects poverty (coefficient = 0.244), suggesting that increased gender inequality contributes to worsening poverty. Additionally, GII directly negatively affects GRDP per capita (coefficient = -0.269), implying that regions with greater gender disparities tend to have lower economic performance. The study also confirms an indirect effect, where gender inequality exacerbates poverty, depressing economic productivity and growth. These findings underscore the importance of integrating gender equality into economic development strategies. To achieve inclusive and sustainable economic growth, policies must reduce gender-based barriers in education, employment, and healthcare, empowering women to contribute fully to economic development and poverty reduction.